2018
DOI: 10.1089/omi.2018.0033
|View full text |Cite
|
Sign up to set email alerts
|

Genomics and Epigenomics of Congenital Heart Defects: Expert Review and Lessons Learned in Africa

Abstract: Congenital heart defects (CHD) are structural malformations found at birth with a prevalence of 1%. The clinical trajectory of CHD is highly variable and thus in need of robust diagnostics and therapeutics. Major surgical interventions are often required for most CHDs. In Africa, despite advances in life sciences infrastructure and improving education of medical scholars, the limited clinical data suggest that CHD detection and correction are still not at par with the rest of the world. But the toll and geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 180 publications
0
21
0
Order By: Relevance
“…The same CHD phenotype can be caused by different mutations, and the same mutation may lead to different phenotypes in different patients (32). The occurrence of CHD is a complex process, involving genetic and environmental factors, epigenetic regulation and many other factors (33). In conclusion, the results of the present study may broaden the spectrum of known mutations in the GATA4 gene associated with congenital heart defects, and could provide novel insights into the mechanism underlying CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The same CHD phenotype can be caused by different mutations, and the same mutation may lead to different phenotypes in different patients (32). The occurrence of CHD is a complex process, involving genetic and environmental factors, epigenetic regulation and many other factors (33). In conclusion, the results of the present study may broaden the spectrum of known mutations in the GATA4 gene associated with congenital heart defects, and could provide novel insights into the mechanism underlying CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the genetics of CHD specific to LMIC is nearly nonexistent. A comprehensive review by Thomford et al found that the vast majority of studies focused on phenotypes of CHD in Africa did not include genetic investigation (Thomford et al, 2018). There were a few African studies that showed that GATA4 (P193H), MTHFR 677TT, and MTHFR 1298CC were associated with atrial septal defect, ventricular septal defect, Tetralogy of Fallot, and patent ductus arteriosus F I G U R E 1 Global map showing percent of population living in multidimensional poverty (Alkire & Robles, 2015) (Al-Azzouny et al, 2016;Zidan, Rezk, & Mohammed, 2013).…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…Next generation sequencing has become a powerful technology, both in the clinical and research setting, facilitating the interrogation of the entire exome or genome with massive parallel sequencing (Kruszka, Tanpaiboon, et al, 2017;Thomford et al, 2018). The major challenge of NGS is the growing amount of data generated that demands complex algorithms to analyze (Bien et al, 2019).…”
Section: Next Generation Sequencing (Ngs)mentioning
confidence: 99%